Space Planting, Competition, and Productivity of a Seven-Year-Old Clonal Teak Plantation in the East Java Monsoon Forest Area - Rika Bela Rahmawati; Suryo Hardiwinoto; Widiyatno; Budiadi; Yahya Amin; Hasanusi Hasanusi (Jurnal Manajemen Hutan Tropika, 2021)
Tree breeding of teak results in selected clones with high growth. Intensive silviculture is required to support a large-scale clonal teak plantation. Appropriate spacing is one of the methods to increase forest plantation productivity. Research of teak clone spacing was conducted on a seven-year-old clonal teak plantation with randomized completely block design. The treatments tested in this study were four plant spacing distances, namely, 3 m × 3 m, 6 m × 2 m, 8 m × 2 m, and 10 m × 2 m. Results show that spacing had significantly different effects on diameter, height, bole height, branch angle, crown area, crown projections, volume, and competition index. However, the height growth did not exhibit any significant differences. The 10 m × 2 m spacing produced the best diameter growth, crown area, and competition index, but has a low volume per hectare and the lowest height of free branch and branch angle. Meanwhile, the 3 m × 3 m spacing will increase bole height and stand volume per hectare. This result suggests that spacing could improve the growth of teak clone but must be followed by intensification of proper maintenance to reduce branch angle and increase bole height.